Importance of Employability Skills as Perceived by Employers of Malaysian Manufacturing Industry - A. P., Puvanasvaran (2009)
technical skills and should be acquired by an employee in the industrial sector today. Unfortunately not all employees today acquired employability skills that are expected by the employer. This study is carried out to identify aspects of the employability skills and its relationship with the requirement of the employer in the manufacturing industries. Samples for the research consist of 107 employers from manufacturing industry and this study has been done to companies in the manufacturing industry and grouped into three which are type of industry, company size and ownership status. Analysis of the survey, managed to determine important aspects of the employability skills needed by employers in the manufacturing industries. The skills were ranked and results showed that all seven of the employability were considered important by Malaysian manufacturing industry with the basic skill, thinking skill, sources skill, resources skill, system and technology skill and personal qualities were most important skills whereas informational skill was considered moderately important.